DIGITAL PLATFORMS AND SMART TOURISM ECOSYSTEMS: OPPORTUNITIES AND CHALLENGES - Feruz Karimov (Journals Park Publishing, 2024)
Digital technologies linked to Industry 4.0 are transforming the tourism sector, giving rise to smart tourism ecosystems where data and platforms play a central role. This paper explores how digital platforms such as online travel agencies, peer-to-peer services, review websites, meta-search tools, mobility apps, and social media shape these ecosystems. The study highlights the main opportunities created by digital transformation, including efficiency, personalization, global market access, and improved governance. At the same time, it points out critical challenges such as digital inequality, market concentration, data privacy risks, regulatory gaps, and the problem of overtourism. By analyzing both benefits and risks, the paper contributes to a clearer understanding of the dual role of digital platforms in tourism development. It also provides practical recommendations for destinations and businesses to use digital tools in ways that support innovation, competitiveness, and long-term sustainability.
Keywords: Smart tourism, digital platforms, Industry 4.0, online travel agencies, peer-to-peer economy, social media, big data, artificial intelligence, sustainability, governance.